EVALUASI KINERJA GURU DALAM PEMBELAJARAN MATEMATIKA SEKOLAH DASAR MENGGUNAKAN MODEL CHARLOTTE DANIELSON - Protario Prima Yudistira; Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher performance is a key factor in determining the quality of mathematics instruction in elementary schools. This study aimed to evaluate teachers’ performance in mathematics learning at SD Negeri 2 Temurejo using the Charlotte Danielson Model. A mixed-methods approach with a sequential explanatory design was employed. The quantitative phase involved six classroom teachers from grades I–VI selected through total sampling. Data were collected through observations, questionnaires, interviews, and documentation based on four domains: Planning and Preparation, Classroom Environment, Instruction, and Professional Responsibilities. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data condensation, data display, and conclusion drawing. The results showed that Planning and Preparation reached 79.2% and was categorized as good, while Classroom Environment reached 83%, Instruction 82%, and Professional Responsibilities 84%, all categorized as very good. Professional Responsibilities achieved the highest score, whereas Planning and Preparation obtained the lowest. Teachers demonstrated strengths in subject-matter knowledge, formulation of learning objectives, classroom management, feedback provision, instructional reflection, and communication with parents. However, improvements are still needed in instructional model variation, learning media utilization, systematic learning activity design, questions promoting mathematical reasoning, technology use, and continuous professional development. These findings indicate that the Charlotte Danielson Model provides a comprehensive framework for evaluating teacher performance and identifying priority areas for improving the quality of mathematics instruction in elementary schools.